Pengaruh Formulasi Media dan Konsentrasi Air Kelapa terhadap Pertumbuhan Protokorm Anggrek Phalaenopsis In Vitro - Lisa Erfa; Yuriansyah Yuriansyah (Politeknik Negeri Lampung., 2012)
The objective of this research was to find combination of media formulation and coconut water consentrasions in stimulating in vitro Growth of Phalaenopsis protocorm. The research was conducted in Factorial Completely Randomaized Design. The first factor is the media formulation (Knudson C, fertilizer Vitabloom, Green Kristallon , and Grownmore). The second factor is coconut water consentrasion (0, 75, 150, 225 ml l-1). Each treatment combination was replicated three times. The result showed that(1) Vitabloom and green kristallon fertilizers gave a better significant growth of seedling height than Grownmore but no significant difference with Knudson C; (2) the additions of Coconut water 225 ml l-1gave the best in growth of height seedling, followed by coconut water 150 ml l-1; and (3) the best treatment combination was green kristallon with coconut water 150 ml l-1, followed by vitabloom and green kristallon added with coconut water 225 ml l-1. Keywords: Formulation media, coconut water, protocorm, Phalaenopsis, in vitro.